Follow the leader: Identity leadership and moral behaviour in social situations among youth sport teammates. (July 2021) - McLaren, Colin D.; Boardley, Ian D.; Benson, Alex J.; Martin, Luc J.; Fransen, Katrien; Herbison, Jordan D.; Slatcher, Richard B.; Carré, Justin M.; Côté, Jean; Bruner, Mark W.
Abstract: Objectives: Although social identity has been linked to moral behaviour in past research, we know less about how the identity-enhancing behaviours of athlete leaders may relate to the experience of prosocial and antisocial behaviour between youth sport teammates. This study examined the relations between perceptions of athlete identity leadership and moral behaviour in social situations outside of training and competition. Methods: Participants were 130 competitive male and female youth ice hockey players ( M age = 13.45 years, SD = 1.82, range = 10–17) from nine teams in a Northeastern Ontario city in Canada. Measures of identity leadership and moral behaviour were completed concurrently within the final three weeks of the regular season. Results: Using structural equation modeling, results demonstrated a significant positive association between identity leadership and both engaging in prosocial behaviour toward teammates ( β = .37, p = .003) and receiving prosocial behaviour from teammates ( β = 0.40, p < .006), accounting for 34% and 51% of the variance in each prosocial outcome, respectively. Although the relations with antisocial behaviour (engaged and received) were in the expected negative direction, the path estimates were not significant ( p s > .23). Conclusion: These findings further our understanding of identity leadership in youth sport generally, offering insight into the relations between identity-enhancing athlete leader behaviours and moral behaviour. The findings also extend past moral behaviour research to consider the social situations in which teammates find themselves outside of training and competition. Highlights: Investigated identity leadership and teammate moral behaviour in social situations. Identity leadership positively predicted prosocial behaviours among teammates. Identity leadership was not significantly associated with antisocial teammate behaviours. Consistent results for both engaging in, and receiving, moral behaviour from teammates.